Day 2 Thu, September 11, 2014 2014
DOI: 10.2118/170297-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Buckling Analysis of a Riserless Drillstring

Abstract: The increasing demand for exploration of deepwater reservoirs poses significant challenges for operators, well planners, and drilling engineers. As a recently developed deepwater drilling technology, riserless drilling offers numerous advantages over traditional riser-based drilling. However, riserless drilling is accompanied by substantial operational challenges, one of which is buckling of drillstrings. Buckling failure occurs when the drillstring misses an existing wellhead or experiences excessive torque a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Li et al 12 analyzed the 3D vibration fatigue life of drill string in deep-water riserless drilling on the basis of Miner's linear cumulative damage law. Li and Collins 13 reported that excessive weight on bit (WOB) may cause the buckling of the drill string at the wellhead when carry out riserless drilling in shallow water. Han et al 14 developed a mechanical model of drill string in water by considering the working environment of a drill string during deep-water riserless drilling.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 12 analyzed the 3D vibration fatigue life of drill string in deep-water riserless drilling on the basis of Miner's linear cumulative damage law. Li and Collins 13 reported that excessive weight on bit (WOB) may cause the buckling of the drill string at the wellhead when carry out riserless drilling in shallow water. Han et al 14 developed a mechanical model of drill string in water by considering the working environment of a drill string during deep-water riserless drilling.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers published work on improving joints of drilling tools anti-fatigue life. They mainly focused on the issue of drilling tools material itself, [12][13][14] and modifying the thread structure or investigating on how the stress concentration factor and the notch sensitivity factor changing with different thread structures, [15][16][17] which provides a theoretical basis for the modification of the joint of drilling tools to improve their anti-fatigue life.…”
Section: Introductionmentioning
confidence: 99%